Student Perceptions of Learning Clinical Masking in Audiology: An Exploratory Survey Study - Skinner, Kimberly; Billingsly, Danica; Conley, Quincy (American journal of audiology, 2023)
The audiology literature is rich with work in the area of clinical masking, yet there is a perception that learning how to mask is difficult. The purpose of this study was to explore the experiences of audiology doctoral students and recent graduates in learning clinical masking. This exploratory study used a cross-sectional survey design, sampling doctor of audiology (AuD) students and recent graduates to probe the perceived effort required and challenges experienced in learning clinical masking. A total of 424 survey responses were included in the analysis. A large majority of respondents rated learning clinical masking as being challenging and effortful. Responses suggested that it took more than 6 months for confidence to develop. Qualitative analysis of the open-ended question uncovered four themes: "negative experience in the classroom"; "lack of consensus or variation in teaching"; "focus on content/rules"; and "positives, internal and external." Survey responses shed light on the perception that clinical masking is difficult to learn and highlight teaching and learning strategies that affect the development of this skill. Students reported a negative experience when significant emphasis was placed on formulas and theories and when encountering multiple masking methods in the clinic. On the other hand, students found clinic, simulations, lab-based classes, and some classroom instruction beneficial to learning. Students reported that their learning process included use of cheat sheets, practicing independently, and conceptualizing the process of masking to support their learning.